Gender ideologies in English and Slovene - Plemenitaš, Katja (ELOPE (Ljubljana), 2014)
The article deals with the concept of linguistic sexism in the cross-cultural context. It compares the generally accepted guidelines for avoiding linguistic sexism in English and Slovene, exemplified by two guides on non-sexist use of English. It is argued that in English non-sexist language strives for gender neutrality, whereas in Slovene it strives for gender specificity. The reasons for the differences between the perceptions of sexism in English and Slovene are examined by taking into account the linguistic expression of gender and the cultural and historical context in which both languages have developed. The use of semantic gender in English, as opposed to the use of grammatical gender in Slovene, is treated as one of the factors influencing the approach to the non-sexist use of language in both languages. Strategies for non-sexist expression and their rebuttals are discussed in the context of predominant cultural ideologies about gender and presuppositions regarding the link between social change and linguistic reform.
Keywords: angleščina; English; jezik; Language; neseksistična jezikovna raba; seksizem; Slovene; slovenščina; spol